The cybercrime sanctions within both European Union and West African states - (:unkn) unknown (My University, 2015)
Each party of the space, realized by the ground, maritime or air borders is desired by the nations which succeed in making it private grounds with the exception of a single component: the cyberspace. This place of exchanges and circulation of information freed itself from this cornering. It is what makes it real for the uses which it allows (sendings of messages, broadcasting) of real-time information, trainings and virtual (as far as the digital networks follow with difficulty localizable paths) in the point to generate difficulties as for its frame by the law. From then on, the cyberspace sets up itself as a space where it is easy to cultivate illegal activities considering the opportunities which it offers. The illegal activities marry forms pluridimensionnelles and complex which we group under the generic naming of cybercrime. Due to its nature and its subdivisions, the cybercrime is the object of reflections, studies, searches, implementations of politics and of actions in a national and international scale to reach in his eradication. The actions are led in way coordinated between States and institutions. The fight against this interplanetary phenomenon requires the mutualization of the efforts on behalf of the actors of telecommunications, computing, all the professional layers as well as her on behalf of the consumers under reserve that they are informed well about the risks connected for the cyberspace. The study compared by the systems of repression implemented in the European and West-African spaces will allow to understand better the exercise of the penal sovereign right in front of the cybercrime and the importance of collaborations between these two community spaces.
Keywords: African Research